(untitled) (Malaysian Management Journal, 2016)
The Consumer buying criterion has reformed massively in this present digitized marketing environment. The growing importance & popularity of online buying is very much substantial and quite evident in India these days. This study attempts to investigate the relationships between brand trust, social linkages, brand awareness, online retail brand engagement and final brand selection & purchase intention. The current research also examined the linkages among brand trust, social linkages, brand awareness and online retail brand engagement and in creating the final brand selection & purchase intention relating to Indian online retail market. Data from 252 observations were analyzed using the structural equation modeling method. The outcome of this research paper shows how an effective online retail brand engagement environment can be created to boost the final brand selection & purchase intention in the Indian online market place.